pathology of cardiac disorders in pigs reared on swill - Sivanesan P (Centre of Excellence in Pathology, College of Veterinary and Animal Sciences, 2005)
Pig rearing in rural production systems based on the swill feed has become very popular in Kerala. The cases of sudden mortality in apparently healthy animals and earlier reports of the cardiovascular damages in such animals prompted to study the effects of swill feed on the cardiovascular system in pigs. The study confirmed, the cardiomyopathies are more common in the pigs which were maintained on swill than those maintained on concentrate feed. Cardiac lesions to the tune of 46.2% were observed in swill fed pigs examined compared to a mere 6.1% cases in concentrate fed pigs. The cardiac lesions recorded were varying degrees of congestion, hemorrhage, hydropericardium, hemopericardium, fibrinous pericarditis, myocardial degeneration, cardiac hypertrophy, cardiac dilatation and valvular endocarditis. The histopathological changes of all these conditions have been studied in detail and the possible pathogenesis described. The vascular changes associated with myocardial necrosis have to be studied in detail by more controlled experimental study. The pathological changes associated with various cardiac disorders are suggestive of multiple nutritional deficiencies. The serum enzyme levels of AST, LDH and CK were found to be higher in swill fed pigs with cardiomyopathic changes than that of serum of pigs reared on concentrate feed. The high enzyme level in the absence of any gross changes in the heart indicated that these could be used as marker for monitoring the subtle cardiomyopathic changes. The various observation made in the study highlighted that the general and immune status of swill fed animals needs to be studied in the light of pathological changes and the subtle changes reflected by the elevated enzyme levels. The result of the study also highlights the need to monitor the nutrient content of the swill, especially the availability of micronutrients.